A novel neutron spin echo technique for measuring phonon linewidths using magnetic Wollaston prisms. (1st December 2014) - Li, Fankang; Pynn, Roger
<x xml:space="preserve">Abstract</x> A new method of implementing neutron spin echo measurement of phonon linewidths on a triple‐axis neutron spectrometer is introduced, based on recently developed superconducting magnetic Wollaston prisms. Each arm of the spectrometer is composed of two Wollaston prisms with a rectangular field region between them. By introducing triangular and rectangular field regions, loci of constant spin echo phase can be manipulated easily to achieve the so‐called phonon focusing condition. Unlike the neutron resonance spin echo method, which is tuned by physically tilting the field boundaries, the new device can be tuned electromagnetically to achieve the phonon focusing condition. By adjusting the field configurations, the linewidths of phonon excitations with high energy and large group velocity can be measured. By employing superconducting films to define the various field regions, high neutron transmission and good neutron polarization efficiency can be obtained.